Comparison of Maxillary and Mandibular Incisor Inclination in Class II Division 1 Malocclusion among Chinese Children - Bajracharya, Manju (Orthodontic Journal of Nepal, 2013)
Objective: To determine maxillary and mandibular incisor inclination in Class II Division 1 malocclusion among different vertical skeletal type Chinese children. Materials & Method: Lateral cephalograms of Class II Division I malocclusion cases of 120 Chinese children (male-55, female-65) of the age range 12-14 years were divided into three vertical skeletal types (low angle, average angle, high angle) based on Sella-Nasion to Mandibular plane angle. To determine incisor inclination, lateral cephalometric radiographs were measured and analyzed using factorial analysis. All angular parameters were processed using ANOVA and t-test. Maxillary and mandibular incisor inclinations were discussed in detail among three vertical facial skeletal types. Result: The maxillary and mandibular incisors of low angle individuals were found to be proclined more than those with high and average angle individuals. Conclusion: Different vertical facial types of Class II Division I malocclusion in early permanent dentition accord to establish discriminate values to set up the cephalometric standards for diagnosis and treatment planning for the clinicians.